Taxing by Default - Satterthwaite, Emily (McGill Law Journal / Revue de droit de McGill, 2013)
This paper is the first in the Canadian legal literature to address “tax elections”, which bestow upon taxpayers the ability to choose among two or more available tax treatments for a single taxable event. I argue that policymakers should adopt a rebuttable presumption in favour of setting default treatments according to the preferences of a majority of eligible taxpayers, unless a “penalty default” structure can be shown to convey sufficiently valuable information to the government. To illustrate how such a presumption would work in practice, I apply it to two similar but inconsistently structured tax elections in the Income Tax Act relating to transfers of property to a spouse and to a corporation (subsections 73(1) and 85(1), respectively). I find that the design of subsection 73(1) is sound—its majoritarian default of tax-deferring “rollover” treatment avoids unnecessary transaction costs and squanders no information-forcing role. On the other hand, subsection 85(1) is counter-majoritarian, and the information disclosed jointly by taxpayers and corporations via the 85(1) election can be obtained at lower cost by requiring corporations to routinely report information about contributions of property. Mandatory reporting would also bolster the government’s anti-avoidance efforts. Thus, amending subsection 85(1) to reverse its default treatment would make an important corner of the income tax less costly and, at the same time, more equitable.